Extraspinal Type I Dural Arteriovenous Fistula with a Lumbosacral Lipomyelomeningocele: A Case Report and Review of the Literature - Khaled M. Krisht; Michael Karsy; Wilson Z. Ray; Andrew T. Dailey (Case Reports in Neurological Medicine)
Seven cases of adult spinal vascular malformations presenting in conjunction with spinal dysraphism have been reported in the literature. Two of these involved male patients with a combined dural arteriovenous fistula (DAVF) and lipomyelomeningocele. The authors present the third case of a patient with an extraspinal DAVF and associated lipomyelomeningocele in a lumbosacral location. A 58-year-old woman with rapid decline in bilateral motor function 10 years after a prior L4-5 laminectomy and cord detethering for diagnosed tethered cord underwent magnetic resonance imaging showing evidence of persistent cord tethering and a lipomyelomeningocele. Diagnostic spinal angiogram showed a DAVF with arterial feeders from bilateral sacral and the right internal iliac arteries. The patient underwent Onyx embolization of both feeding right and left lateral sacral arteries. At 6-month follow-up, MRI revealed decreased flow voids and new collateralized supply to the DAVF. The patient underwent successful lipomyelomeningocele exploration, resection, AV fistula ligation, and cord detethering. This report discusses management of this patient as well as the importance of endovascular embolization followed by microsurgery for the treatment of cases with combined vascular and dysraphic anomalies.